Protein interactomes of three stress inducible small heat shock proteins: HspB1, HspB5 and HspB8. (22nd May 2013) - Arrigo, André-Patrick; Gibert, Benjamin
Abstract: Purpose : The recent discoveries in the field of human small heat shock proteins (sHSPs) clearly point to the important roles played by these adenosine triphosphate (ATP)-independent chaperones in the regulation of a large spectrum of vital cellular processes and in pathological diseases. These proteins are therefore considered as very attractive therapeutic targets. Aims : To understand the functions of the stress-inducible members of the sHSP family, HspB1, HspB5 and HspB8, and be able to therapeutically modulate their activities, researchers are faced with the complex oligomerisation and phosphorylation properties of these proteins and with their ability to interact with each other and with specific protein targets. Here, we have integrated, in a functionally orientated way, the up-to-date literature data concerning HspB1, HspB5 and HspB8 protein interactions which reflect their numerous crucial cellular functions. We also present data supporting the idea that specific phospho-oligomeric domains of HspB1 are involved in the interaction with particular client proteins. Conclusions : More information concerning the interactions between client protein targets and sHSPs or the multiple combinatorial chimeric oligomeric complexes formed by different sHSPs are urgently required to elaborate a comprehensive sHSPs protein interactome and propose efficient and pathology-specific therapeutic approaches.